A Study of Trauma in The Shadow of Crescent Moon - Shazmeen Nawaz; Dr. Zareena Qasim; Dr. Asifa Qasim (Al-Qanṭara, 2023)
The present study aims at conducting a close analysis of the representation of trauma in contemporary Pakistani fiction. Drawing on the debates of Caruth, LaCapra, and Herman among others, this study analyses The Shadow of Crescent Moon by Fatima Bhutto in order to trace the experiences of the characters undergoing the trauma of war and forced migration in the novel. The novel depicts the people who migrate to a fictional area Mir Ali in Pakistan in the aftermath of the 9/11 war on terror, but these people remain under constant threat of death due to the ongoing tussle between the army and freedom fighters. The study explores the trauma of migrants who are dragged to war grounds against their will. Overall, this study helps in illuminating the human cost of forced migration and trauma, as well as the resilience and adaptation of individuals and communities in the face of adversity. Keywords: War, Forced Migrations, Loss, Trauma, Pakistani Fiction